PENGARUH BERBAGI PENGETAHUAN TERHADAP KINERJADEPARTEMEN MELALUI INOVASI JASA/PELAYANAN - RAMADHAN TRI WAHYUNI, RISTA (Jurnal Ilmu Manajemen (JIM), 2013)
Industrial world competition requires company to be morecompetitive by building knowledge based organization to performknowledge sharing activity. This study is aimed to test and analyze ifknowledge sharing activity that consist of knowledge donating andknowledge collecting applied would affect to department’sperformance through servce innovation at Service Management PTTelkomsel, Tbk. The study type used is exploration study withquantities descriptive, while sampling of 30 respondents. Thestatistical analysis used is Structural Equation Modeling (SEM) withSMART PLS 2.0 software. Correlation between knowledge donating ispositively and significantly influencing service innovation, while ispositively and significantly influencing department’s performance.Correlation of knowledge collecting is positively and significantlyinfluencing service innovation but not significantly influencingdepartment’s performance. Service innovation is not mediating thecorrelation of knowledge donating to department’s performance, whileis mediating knowledge collecting to department’s performance.Keywords: knowledge donating, knowledge collecting, service innovation, department’s performance.